Dude, everyone wants pattern analysis tools (DEWPAT): Tools for measuring visual pattern complexity from digital images - Jillian A. Sanderson; Tristan Aumentado‐Armstrong; Charles‐Olivier Dufresne‐Camaro; D. Luke Mahler (Methods in Ecology and Evolution)
Abstract Understanding the diversity and function of complex colour patterns is a fundamental interest in ecology and evolutionary biology, but progress on many questions is limited by our ability to quantify diverse visual patterns. We address this problem by introducing Dude, Everyone Wants Pattern Analysis Tools (DEWPAT), a Python package for characterizing multidimensional pattern complexity. DEWPAT is a flexible framework designed to extract a diversity of components of visual pattern complexity from standard RGB and multispectral images, including information entropy, edge content (average gradient magnitude), high frequency content (detail granularity), heterogeneity and patch dissimilarity. DEWPAT offers image transformation functionality, including blurring to model receiver acuity and segmentation to reduce noise. Functions in this package return both quantitative measurements and graphical representations of colour and pattern diversity. We demonstrate DEWPAT's key functions and applications with three empirical examples (longhorn beetles, anole lizards and flowers). DEWPAT has the potential to quantitatively characterize complex pattern phenotypes in ways that make their features available for biological analysis.